Epigenetic silencing of CYP24 in the tumor microenvironment - Johnson, C.S.; Chung, I.; Trump, D.L. (2010)
Calcitriol (1,25 dihydroxycholecalciferol) has significant anti-tumor activity in vitro and in vivo in a number of tumor model systems. We developed a system for isolation of fresh endothelial cells from tumors and Matrigel environments which demonstrate that CYP24, the catabolic enzyme involved in vitamin D signaling, is epigenetically silenced selectively in tumor-derived endothelial cells (TDEC). TDEC maintain phenotypic characteristics which are distinct from endothelial cells isolated from normal tissues and from Matrigel plugs (MDEC). In TDEC, calcitriol induces G(0)/G(1) arrest, modulates p27 and p21, and induces apoptotic cell death and decreases P-Erk and P-Akt. In contrast, endothelial cells isolated from normal tissues and MDEC are unresponsive to calcitriol-mediated anti-proliferative effects despite intact signaling through the vitamin D receptor (VDR). In TDEC, which are sensitive to calcitriol, the CYP24 promoter is hypermethylated in two CpG island regions located at the 5'end; this hypermethylation may contribute to gene silencing of CYP24. The extent of methylation in these two regions is significantly less in MDEC. Lastly, treatment of TDEC with a DNA methyltransferase inhibitor restores calcitriol-mediated induction of CYP24 and resistance to calcitriol. These data suggest that epigenetic silencing of CYP24 modulates cellular responses to calcitriol. (C) 2010 Elsevier Ltd. All rights reserved.